Beginning VB 2008 Databases From Novice to Professional - Vrat Agarwal, Vidya; Huddleston, James (Apress : Imprint: Apress, 2008)
Beginning VB 2008 Databases teaches you everything you need to know about relational databases, SQL, and ADO.NET 2.0, giving you a sound start in developing console and Windows database applications. The book also includes chapters on the SQL Server XML data type and the LINQ enhancements to the next version of Visual Basic. In addition to teaching you database basics like using SQL to communicate with databases, this book provides you with detailed, code-practical techniques to access data in Visual Basic 2008 across a range of coding situations. Code-heavy and full of practical detail, this book has been fully revised and upgraded for .NET 3.5 and offers you the best contemporary practice in this core programming area, so that you'll find yourself using it in nearly all your .NET projects. Provides step-by-step instructions on how to install and configure necessary tools Presents all essential SQL query and update concepts and syntax, so you don't need prior familiarity with relational databases or SQL Describes how to use ADO.NET transactions, exceptions, and events Covers ADO.NET features for handling XML, text, and binary data within a Visual Basic 2008 context Explains all concepts through straightforward code examples.